PRIVATIZATION OF HOUSING AND COMMUNAL SERVICE ENTERPRISES: PRIVATIZATION MECHANISM AND PROPERTY EVALUATION - G. G. Kuznetsova (Модернизация, инновация, развитие)
Housing and communal services in Russia are provided by state or municipality owned so-called unitary enterprises. At present, most of these enterprises are at the brink of bankruptcy. Privatization in the field of housing and communal economy (HCE) sector is one of most efficient instruments of improvement thereof. Particular feature of the author’s approach to evaluation of the total or partial cost of such enterprises is summing up the values of the element-to-element property assessment on the basis of the enterprise’s net assets. Described in the article is a system and succession of steps to be followed by private entities formed on the basis of HCE enterprises’ whole or partial property or acquiring rights thereupon.